The Use of Creating Stories in Teaching Writing for The Fifth Grade Students at Sdn Jombor 01 Bendosari Sukoharjo - Nurnaningsih; Veronika Unun Pratiwi; Arin Arianti (Faculty of Language and Literature, University of Surakarta, 2019)
The purpose of this research is to determine the application of creating stories in the teaching of writing a good English text and to know the most favorite media used by the fifth grade students at SDN Jombor 01 in writing an English text. The interesting teaching technique makes students easier to write a simple English text. The method used in this research is a qualitative. In this research, results and discussions are illustrated with the description. The results of English writing work are data taken at SDN Jombor 01 Bendosari Sukoharjo. Data collection is done by observation and documentation. Basically the implementation of creating stories can be done by picture series and bubble. Creating stories help students to write English stories then they present it in front of the class. The most favorite media used by the fifth grade students at SDN Jombor 01 Bendosari Sukoharjo is the picture series.